Deep Species Distribution Modeling From Sentinel-2 Image Time-Series: A Global Scale Analysis on the Orchid Family - Estopinan, Joaquim; Servajean, Maximilien; Bonnet, Pierre; Munoz, François; Joly, Alexis (Frontiers in Plant Science, 2022)
Species Distribution Models (SDMs) are widely used numerical tools that rely on correlations between geolocated presences (and possibly absences) and environmental predictors to model the ecological preferences of species. Recently, SDMs exploiting deep learning and remote sensing images have emerged and have demonstrated high predictive performance. In particular, it has been shown that one of the key advantages of these models (called deep-SDMs) is their ability to capture the spatial structure of the landscape, unlike prior models. In this paper, we ask whether the temporal dimension of remote sensing images can also be exploited by deep-SDMs. Indeed, satellites such as Sentinel-2 are now providing data with high temporal revisit and it is likely that the resulting time-series of images contain relevant information about the seasonal variations of the environment and vegetation. To confirm this hypothesis, we built a substantial and original dataset (called DeepOrchidSeries) aimed at modelling the distribution of orchids on a global scale based on Sentinel-2 Image Time-series. It includes around 1 million occurrences of orchids worldwide, each being paired with a twelve-month-long time-series of high resolution images (640 x 640 m RGB+IR patches centered on the geolocated observations). Thanks to this ambitious dataset, we trained several deep-SDMs based on Convolutional Neural Networks (CNNs) whose input was extended to include the temporal dimension. To quantify the contribution of the temporal dimension, we designed a novel interpretability methodology based on temporal permutation tests, temporal sampling and temporal averaging. We show that the predictive performance of the model is greatly increased by the seasonality information contained in the temporal series. In particular, occurrence-poor species and diversity- rich regions are the ones that benefit the most from this improvement, revealing the importance of habitats temporal dynamics to characterise species distribution.